The Cost of Emotions in the Workplace : Bottom Line Value of Emotional Continuity Management - Hawkins Mitchell, Vali, 1949-; Noakes-Fry, Kristen (Brookfield, Conn. : Rothstein Associates, 2013)
Shows how to systematically manage your organizational emotional culture. Introduces Emotional Continuity Management and provides tested system to observe, predict, prepare, and write policy to prevent employee problems. Offers tools to quantify costs of disruptive emotional incidents, from bad managers, office bullies to workplace violence.
8. Where Are We Going?Epilogue; References and Links; Glossary; Index; About the Author; Back Cover.
Title from title screen.
Includes bibliographical references.
Keywords: Psychology, Industrial; Personnel management; Emotions; Organizational behavior; Crisis management; Crisis management; Emotions; Organizational behavior; Personnel management; Psychology, Industrial